Non-Smooth Behavior of Reinforced Concrete Beam Using Extended Finite Element Method - Eman Abbas; Alaa H. Al-Zuhairi (Salehan Institute of Higher Education, 2019)
Flexure members such as reinforced concrete (RC) simply supported beams subjected to two-point loading were analyzed numerically. The Extended Finite Element Method (XFEM) was employed for the treatment the non-smooth h behaviour such as discontinuities and singularities. This method is a powerful technique used for the analysis of the fracture process and crack propagation in concrete. Concrete is a heterogeneous material that consists of coarse aggregate, cement mortar and air voids distributed in the cement paste. Numerical modeling of concrete comprises a two-scale model, using mesoscale and macroscale numerical models. The effectiveness and validity of the Meso-Scale Approach (MSA) in modeling of the reinforced concrete beams with minimum reinforcement was studied. ABAQUS program was utilized for Finite Element (FE) modeling and analysis of the beams. On the other hand, mesoscale modeling of concrete constituents was executed with the aid of ABAQUS PYTHON language and programing using excel sheets. The concrete beams under flexure were experimentally investigated as well as by the numerical analysis. The comparison between experimental and numerical results showed that the mesoscale model gives a better indication for representing the concrete models in the numerical approach and a more appropriate result when compared with the experimental results.